2008
DOI: 10.1002/qj.338
|View full text |Cite
|
Sign up to set email alerts
|

Two‐way one‐dimensional high‐resolution air–sea coupled modelling applied to Mediterranean heavy rain events

Abstract: South-eastern France is prone to heavy rain events during the autumn. For these extreme precipitation events, the Mediterranean Sea fuels the atmospheric boundary layer in heat and moisture and sometimes contributes to flooding, owing to the large swell and waves produced in these situations. The aim of this study is to examine how the severe atmospheric conditions over the sea associated with these events alter the ocean mixed layer, and what feedback the ocean contributes to the precipitation events.To addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…In response to strong low-level wind blowing towards the coasts during HPEs, a rapid sea level rise may be observed and significantly amplify the flooding by countering the river runoff to the sea (Lebeaupin Brossier et al, 2009a. Sometimes, at the same time, due to heavy rainfall, a rapid surface freshening occurs (Lebeaupin Brossier et al, 2009a,b, 2012.…”
Section: Introductionmentioning
confidence: 98%
“…In response to strong low-level wind blowing towards the coasts during HPEs, a rapid sea level rise may be observed and significantly amplify the flooding by countering the river runoff to the sea (Lebeaupin Brossier et al, 2009a. Sometimes, at the same time, due to heavy rainfall, a rapid surface freshening occurs (Lebeaupin Brossier et al, 2009a,b, 2012.…”
Section: Introductionmentioning
confidence: 98%
“…On one hand, efforts have been devoted to the assessment of the predictive ability of meteorological models with respect to severe rainfall events (Petroliagis et al, 1997;Romero et al, 2005;Hohenegger et al, 2006Hohenegger et al, , 2008Davolio et al, 2007;Schär, 2007a, 2007b;Argence et al, 2008;Lebeaupin et al, 2008;Amengual et al, 2009;Lapeyre and Talagrand, 2009): their goal is to evaluate how closely a particular model can predict the true state of a certain severe rainfall scenario as a function of observational data quality and availability, parametrization of the subgrid processes, model coupling, model approximations and resolution. On the other hand, some studies have investigated the dynamical, kinematical and microphysics properties of observed systems (Leckebusch and Ulbrich, 2004;Grazzini, 2007;Miglietta and Regano, 2008;Sanchez-Gomez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous numerical modelling experiments on flash-floods have been conducted in this area in recent years. Some of these experiments have been focused on sensitivity testing (Federico et al, 2008;Bresson et al, 2009), development of forecasting systems (Davolio et al, 2009), air-sea interaction processes (Pastor et al, 2001;Lebeaupin et al, 2006Lebeaupin et al, , 2009 or investigation of the mechanisms involved in heavy rain events (Miglietta and Regano, 2008).…”
Section: Introductionmentioning
confidence: 99%